Blended learning - an opportunity to take the best of both worlds - Lapuh Bele, Julija; Rugelj, Joze (International Journal of Emerging Technologies in Learning (iJET), 2007)
The paper presents theoretical foundations for effective ICT supported learning content development and course design. The practical use of these tools is described in the development of blended learning courses for improvement of computer literacy of unemployed people in Slovenia. The results of the survey about the efficiency of learning within these courses and about user satisfaction in the described courses are also presented. Findings indicate that a great majority of the participants of the courses find blended learning a convenient and efficient approach to learning and that most of them plan to use it for learning in the future.